The Impact of Gut Microbiota on Radiation-Induced Enteritis - Jian, Yongping; Zhang, Dan; Liu, Mingdi; Wang, Yishu; Xu, Zhi-Xiang (Frontiers in Cellular and Infection Microbiology, 2021)
Radiotherapy is an important treatment for abdominal tumors. A critical side effect for this therapy is enteritis. In this review, we aim to summarize recent findings in radiation enteritis, in particular the role of gut microbiota dysbiosis in the development and therapy of the disease. Gut microbiota dysbiosis plays an important role in the occurrence of various diseases, such as radiation enteritis. Abdominal radiation results in changes in the composition of microbiota and reduces its diversity, which is mainly reflected in the decrease of Lactobacillus spp. and Bifidobacterium spp. and increase of Escherichia coli and Staphylococcus spp. Gut microbiota dysbiosis aggravates radiation enteritis, weakens intestinal epithelial barrier function, and promotes inflammatory factor expression. Pathogenic Escherichia coli induce the rearrangement and redistribution of claudin-1, occludin, and ZO-1 in tight junctions, a critical component in intestinal epithelial barrier. In view of the role that microbiome plays in radiation enteritis, we believe that intestinal flora could be a potential biomarker for the disease. Correction of microbiome by application of probiotics, fecal microbiota transplantation (FMT), and antibiotics could be an effective method for the prevention and treatment of radiation-induced enteritis.